The gelatinization and retrogradation properties of wheat starch with the addition of stearic acid and sodium alginate. (August 2018) - Yu, Zhen; Wang, Yu-Sheng; Chen, Hai-Hua; Li, Qian-Qian; Wang, Qi
Abstract: The gelatinization and retrogradation properties of wheat starch (WS) with the addition of the combination of stearic acid and sodium alginate (C-SA-AG) were investigated in this study. The results of differential scanning calorimetry (DSC) showed that C-SA-AG significantly increased the gelatinization onset temperature of WS by 2.6–3.4 °C, whereas decreased the gelatinization enthalpy of WS by 5.7–6.7 J/g. This suggested that C-SA-AG could obviously delay the gelatinization process of WS. The gel firmness, retrogradation enthalpy, the ratio of intensity at the band of 1047 cm −1 to 1022 cm −1 (R1047/1022 ), and the relative crystallinity (RC) of WS were significantly decreased with the addition of C-SA-AG by 322–346 g, 0.51–1.78 J/g, 0.06–0.12, and 7.12–9.05% after stored for 7 days at 4 °C, respectively. However, the loss factor (tanδt /tanδ0 ) was increased by 0.49–0.54 after sweeping for 120 min. This suggested that C-SA-AG could effectively retard the retrogradation of WS. During storage, the retrograded WS containing SA showed V-type crystal structure, which lost the A-type crystal structure of native WS. Graphical abstract: Image Highlights: Combination of SA and AG (C-SA-AG) was used to investigate the properties of WS. C-SA-AG delayed the gelatinization process of WS. C-SA-AG could effectively retard the retrogradation of WS. The RC value of WS was decreased with the C-SA-AG. Crystalline structure of retrograded WS with C-SA-AG changed from A-type to V-type.